Processes, networks, and power relations in sub-Saharan Africa - (:unkn) unknown (My University, 2025)
Professor Ricardo Soares de Oliveira joined the Centre for International Studies at Sciences Po in January 2025. Soares de Oliveira has conducted extensive fieldwork on the international political economy of African states, with a focus on extractive industries, the financial sector, conflict and post-conflict reconstruction, and African-Asian relations. In this interview, he answers our questions about his academic career and the research topics that particularly interest him. Interview by Miriam Périer.
Keywords: African Research